The Benefits Of English Song On Students' Language Fluency From The Perspective Of Psychology At Taqifa Kindergarten - Citra Ayu; Putri AsiLestari; Dominikus David Biondi Situmorang (FKIP - Universitas Pahlawan Tuanku Tambusai, 2024)
English language teachers in schools will greatly assist the early learning process of a foreign language, especially if the teacher is able to teach English in a variety of ways, such as by using flashcards, daily conversations and also using technology by showing interesting videos for children. all of these methods aim to improve children's ability to recognize the language. to improve the ability of early childhood in recognizing English. Learning through songs can be used to hone early childhood speaking skills. the process. Learning English through songs can be a in improving students' memory and ability to speak, this can be proven by the ease with which songs are followed and remembered by young children by early childhood.